Penyerapan SDM Lokal pada Usaha Pariwisata di Pantai Duyung, Sanur - Fransiska, Ika Levioni; Sanjiwani, Putri Kusuma (JURNAL DESTINASI PARIWISATA; Vol 12 No 1 (2024): VOL 12, NO 1 (2024): (JANUARY - JUNE) JURNAL DESTINASI PARIWISATA, 2024)
This Study aims Tourism business refers to commercial activities related to the tourism industry. It includes various types of businesses that focus on providing services and facilities to tourists visiting a place or tourist destination. One of the famous tourist areas on the island of Bali is the Sanur Tourist Area. It is called the Sanur Tourist Area because there are several tourist attractions in the Sanur area Duyung Beach is a popular place for tourists and locals to enjoy beautiful natural scenery, engage in sports activities, or simply relax. The aim of this research is to identify the types of tourism businesses that are thriving in Duyung Beach and gather information on the local human resource absorption there. Data collection techniques used include observation, interview, and documentation. The selection of informants was done using purposive sampling technique based on the research objectives. Data analysis used in this research is qualitative descriptive analysis. The availability of local labor with skills and qualifications appropriate to the tourism industry is very important. Local workers in Duyung Beach have relevant skills, so tourism businesses in Duyung Beach will be more likely to employ them rather than looking for workers from outside the area. This research highlights the absorption of local human resources in tourism businesses within the attraction of Duyung Beach, Sanur. The result of this research is to find out how the actual situation is the absorption of local human resources in tourism businesses in Duyung Beach. Keywords: local human resources, tourism business, tourist attractions, duyung beach.